Nordover med filmkamera - fra Wellman til Nobile - Diesen, Jan Anders (Nordlit, 2012)
The Heroic Era in Polar Exploration is filled with fascinating stories about interesting men, and the Race for the Poles is richly described in hundreds of books. The Heroic Era in Polar Exploration coincided with the conception of film technology and rise of commercial cinema, and many polar explorers saw potential in utilising this new technology as a research tool. As a result there exists a range of films from the Polar Explorations, but since their making and initial screenings they have received little attention. The story of these films is also an interesting one, although it has not yet been written. A few years after the production of the first film cameras, the explorer Carsten Borchgrevink brought one along on his British Antarctic Expedition in 1898. His main sponsor, a newspaper publisher, wanted to make news films, but the cinematograph, the film reel and the filming skills were not sufficiently developed to capture living images from the polar region. Our record of this first attempt at making a polar film is limited to one scene from when the expedition is leaving London.The first explorer to succeed in filming in the Arctic was Anthony Fiala in 1902, and since his breakthrough the cinematograph became standard scientific equipment on all polar expeditions. The Mechanical Era in Polar Exploration came with the aeroplanes, the airships and the telegraph. Roald Amundsen played a major role here; he claimed his idea about using aeroplanes was as important to the polar exploration as Nansen´s use of skies and dogsledges in the heroic era. This article tells the story about explorers with film camera trying to reach the North Pole from Spitzbergen. Wellman, Amundsen, Byrd and Nobile are the main characters. The story of their fantastic expeditions is told by others; this is the story about their films, and how the films from the Arctic developed from just documenting landscape and animal life until they became proper documentary films. Between those types of film, we have had amateur film footage, newsreels, scientific films, travelogues and early documentary films. The article ends with describing the media event around the Italia tragedy in 1928.